Diagnostic value of tonsillectomy in positron emission tomography and computerised tomography negative carcinoma of unknown primary - Induchoodan, Meenu; Madhavan, Rajeev Kumar; George, Shibu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Carcinoma of unknown primary (CUP) represents a heterogeneous group of malignancy metastasis unique biology of which remains poorly understood. Even after a complete diagnostic workup including positron emission tomography and computerised tomography (PET-CT) scans the primary site of origin may remain unclear. This case series analysed the diagnostic value of bilateral palatine tonsillectomy in evaluating PET-CT negative head and neck squamous cell CUP. From retrospective analysis of cluster of 68 cases with metastatic cervical nodes with no obvious primary referred for ENT evaluation during a period of 20 months, we identified 5 cases where pan endoscopy and radiological evaluation including PET-CT were negative in detecting the primary. All 5 patients underwent bilateral palatine tonsillectomy along with biopsies from base of tongue and nasopharynx as a part of completion of diagnostic work-up. Tonsillar squamous cell carcinoma was revealed by subsequent histopathology examination in 4 out of 5 patients despite negative PET-CT evaluation. Blind biopsies from other sites like nasopharynx and base of tongue were unfruitful. Our experience strongly emphasises the fact that bilateral palatine tonsillectomy has a high yield in detecting primary even in PET negative CUP, though it needs a larger evidence base.